Constructive Analysis Of Shape. An Important Characteristic Of Pen Art And Imaginative Expression - Abdullayev Alimardon Khaydarovich; Sharabayev Ulugbek Mukhamedovich (Genius Journals, 2025)
This scientific article covers the theoretical and methodological foundations of the constructive analysis of form, the important features of the science of pen drawing in the visual arts, and the psychological, physiological, and graphic mechanisms of the process of figurative expression on a deep scientific basis. The purpose of the research is to determine the geometric structure of the form, analyze proportions based on a mathematical model, reveal the constructive and figurative properties of lines and strokes through scientific criteria, connect the physical and optical laws of the light-shadow system with artistic practice, and study the process of formation of visual perception based on the gestalt principles. It covers the analytical construction of form, generalization mechanisms, spatial construction, visual thinking, compositional stability, the semantic power of lines and strokes in the process of image creation, and the processes of image processing by the brain on a scientific and theoretical basis. This article shows the didactic, psychological and artistic functions of the science of pencil drawing as a single scientific system, and justifies the inextricable link between the constructive analysis of form and figurative expression based on the theories proven in science.
Keywords: constructive analysis; pencil drawing; geometry of form